Statins (HMG-CoA Reductase Inhibitors) Decrease Postoperative Adhesions by Increasing Peritoneal Fibrinolytic Activity - Aarons, Cary B. (2007)
OBJECTIVES: The aims of this study were to determine if statins reduce adhesion formation in vivo and to identify the mechanism of action in vitro. BACKGROUND: Intraperitoneal adhesions develop in up to 95% of patients following laparotomy. Adhesions are reduced by mechanisms that up-regulate fibrinolysis within the peritoneum. Statins promote fibrinolysis in the cardiovascular system and may play a role in the prevention of adhesions. METHODS: Adhesions were induced in rats (n = 102) using our previously described ischemic button model. Rats received vehicle (controls), lovastatin (30 mg/kg), or atorvastatin (30 mg/kg) as a single intraperitoneal dose at the time of laparotomy. Animals were killed and adhesions were quantified at day 7. Peritoneal fluid and tissue were collected at day 1 to measure tissue plasminogen activator (tPA) and plasminogen activator inhibitor-1 (PAI-1) by real-time PCR and ELISA. To assess the effects of statins on wound healing, burst pressures were measured in anastomoses of the colon. The effects of lovastatin on tPA and PAI-1 production were measured in vitro in human mesothelial cells (HMC) in the presence or absence of mevalonate (MVA), geranylgeranyl-pyrophosphate (GGPP) and farnesyl-pyrophosphate (FPP), all intermediates in the cholesterol pathway downstream of HMG-CoA. The effect of a Rho protein inhibitor, exoenzyme C3 transferase, on tPA production was also determined. RESULTS: Lovastatin and atorvastatin reduced adhesion formation by 26% and 58%, respectively (P < 0.05), without affecting anastomotic burst pressure. At 24 hours, tPA mRNA levels in peritoneal tissue and tPA activity in peritoneal fluid from lovastatin-treated animals were increased by 57% and 379%, respectively (P < 0.05), while PAI-1 levels were unchanged. HMC incubated with either lovastatin or atorvastatin showed concentration-dependent increases in tPA production and decreases in PAI-1 production (P < 0.05). These lovastatin-induced changes in tPA and PAI-1 production were significantly reversed by the addition of MVA, GGPP, and FPP. The Rho protein inhibitor increased tPA production and rescued tPA production from the inhibitory effect of GGPP. CONCLUSION: These data suggest that statins administered within the peritoneum can up-regulate local fibrinolysis, while the in vitro studies show that this effect may be mediated, in part, by intermediates of the cholesterol biosynthetic pathway that regulate Rho protein signaling.